CFD analysis on the effect of temperature on gas distribution in indoor environment - Juffry Z.H.M.; Kamarudin K.; Adom A.H.; Abdullah A.N.; Ismail I.N. (IOP Publishing Ltd, 2023)
Air quality; Computational fluid dynamics; Environmental regulations; Smoke; Temperature; Ventilation; Air circulation; CFD analysis; Condition; Effects of temperature; Gas distribution; Indoor environment; Outdoor air qualities; Potential risks; Three dimensional simulations; Ventilation systems; Gases